Mineral nutrition of vegetable crops: XXIX. absorption of nutrients by four strawberry (Fragaria spp) cultivars - Souza, Antonio Francisco; Haag, Henrique Paulo; Sarruge, José Renato; Oliveira, Gilberto Diniz de; Minami, Keigo (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
The aim of this work was to estimate the differences in growth (dry weight basis), nutrients uptake, fruits yield, total uptake and exportation of nutrients among several strawberry cultivars: Campinas (IAC-2712), Camanducaia (IAC-3530), Monte Alegre (IAC-3113) and SH-2. The experimental was carried out in the Escola Superior de Agricultura "Luiz de Queiroz", in field conditions, in 1975/76. The soil belongs to Terra Roxa Estruturada type, and "Luiz de Queiroz" serie. This soil has been cultivated for more than 25 years. The experimental design was that randomized blocks with four replications and analysed together following the design of split-plot. The soil of the plots were revolved to a deep of 12 cm following application of 10 kg organic matter/m². The fertilizers were applied in the groove and in the same amount for all cultivars: Ammonium sulfate (20% N), 10 g/m; triple superphosphate (20% P(2)0(5)) 10 g/m; Potassium cloride (60% K(2)0), 10 g/m. Therty days after planting, 10 g/plant of ammonium sulfate was applied. After 76 days from planting, the firsa sample was taken. Other samples were taken in equal intervals of 20 days, up to 216 days. When a decrease in fruitproduction was noted. The sample (plants) were divided in stems, leaves and fruits and chemical analysis were made for N, R, K, Ca, Mg e S. The variation on production (dry matter) nutrient uptake' and fruits yield, were obtained from data calculated by adjusted regression equation analysis. The maxima point from these equations were taken to show the total nutrient uptake. From the data obtained, the following conclusions could be drawn. Growth - The dry matter of stems, leaves and fruits were different among the cultivars. The production of dry matter by the stems and fruits were linnear for all cultivars up to 196 and 216 days. The highest productions on dry matter varied between 15 to 25 g and 12 to 20 g/plant. The maximum production of dry matter in the leaves among the cultivars varied between 20 to 30 g at 196 and 173 days respectivelly. The cultivars Campinas (IAC-2712) and Camanducaia (IAC-3530) produced more dry matter than SH-2 cultivar. Nutrient uptake -< The were differences on nutrient content in stems and leaves among cultivars (R, K, Ca, S, B) and in the fruits for N, R, K, Mg, S. The highest absorption of nutrients (days after planting) is shown in Table I. Yield - No significant difference in fruit production was observed among the cultivars. The highest yield among the cultivars showed a variation between 103 to 151 g per plant at the 207 and 207 days,